The Role of Culture in Moderating the Influence of Financial Literacy and the Performance of SMEs in North Toraja Regency - Stefani Marina Palimbong; Mince Batara (LP2M IAIN Palopo, 2026)
This research aims to analyze and determine the role of culture in moderating the influence of financial literacy on SME performance. This research uses a quantitative approach. The objects studied were SME owners in Toraja Regency. Data was obtained through a survey with an instrument, namely a questionnaire and the sampling method used was the simple random sampling method. The results of the research conclude that financial literacy has a significant effect on the performance of North Toraja Regency MSMEs and culture can moderate the influence of financial literacy on the performance of North Toraja Regency SMEs.